Επενδύσεις αποθεματικών ασφαλιστικών ταμείων στα πλαίσια της παγκοσμιοποίησης - Νεκτάριος Μιλτιάδης (SPOUDAI Journal of Economics and Business, 2007)
Developed countries try to face the demographic problem by adopting partially funded supplementary pension plans, and /or by accumulating additional reserves in the pay-as-you-go pension systems. International experience shows that the returns on the investments of the pension funds have been adequate so far. Returns are higher in countries that have adopted more liberal investment regulations than in countries with more restrictive practices. In the near future the developed countries will face the problem of where to invest the huge amounts of capital that are currently being accumulated all over the developed world in order to face the pension problem. It is proposed that inevitably these funds will be invested in the younger demographic regions of the third-world developing countries. These pension fund flows will become the main drivers of globalization, which eventually will: (a) contribute to the economic development of third- world and (b) provide the means for financing the increased needs of the retired population in the developed countries. JEL Classifications: G23, H55